PENGEMBANGAN SOFTWARE BERHITUNG DALAM PEMBELAJARAN MATEMATIKA PADA MATERI BANGUN DATAR DAN BANGUN RUANG - LIA SEPTIANI (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2021)
The development of the world of technology at this time has a great influence and impact on the development of educational technology, especially in programming to develop technology in the field of Mathematics. Seeing the development of the world of education, of course, requires educators to be able to use technology that can be used as a learning medium, namely computer technology. Learning media is needed by educators to increase students' interest in learning, simplify the learning process and provide direct practice to students. A real math aid is a calculator that only calculates the basic part of the calculation. This research aims to develop counting software in learning mathematics, especially developing calculators. Research and development is a process used to develop and validate educational products. Research and development used in developing mathematics learning media using a research and development approach by developing learning media can be used as a learning system design model, ADDIE (Analysis Design Develop Implement Evaluate). The results of the media expert test with a value of 3.07, which means it has good criteria, the results of the material expert test with a value of 3.40, which means it has good criteria, the results of the learning design expert test with a value of 3.40 which means it has good criteria. Meanwhile, in the one to one trial with a value of 3.33, which means that it has good criteria, the results of the small group trial with a value of 3.31, which means it has good criteria and the results of the field test test are 3.18. so that the overall average of the expert evaluations and student trials has a percentage of 82.04%, which means that the counting software in mathematics learning which is named the flat and geometric calculator can be categorized as good. ABSTRAKPerkembangan dunia teknologi pada saat ini memberikan pengaruh serta dampak yang besar terhadap perkembangan teknologi pendidikan khususnya pada pemprogaman mengembangan teknologi pada bidang Matematika. Melihat perkembangan dunia pendidikan, tentunya menuntut para pendidik dapat menggunakan teknologi yang dapat digunakan sebagai media pembelajaran ialah teknologi komputer.. Media pembelajaran sangat dibutuhkan oleh para pendidik untuk meningkatkan minat belajar peserta didik, mempermudah proes pembelajaran dan memberikan praktik langsung kepada peserta didik. Alat bantu matematika secara nyata adalah kalkulator yang hanya menghitung bagian dasar dari hitungan. Penenlitian ini bertujuan untuk mengembangkan sotfware berhitung dalam pembelajaran matematika khususnya mengembangan kalkulator. Penelitian dan Pengembangan (research and development) is process used to the develop and validate educational products. Penelitian dan pengembangan yang digunakan dalam mengembangkan media pembelajaran matematika menggunakan pendekatan research and development dengan mengembangkan media pembelajaran dapat digunakan model desain system pembelajaran, ADDIE (Analysis Design Develop Implement Evaluate). Hasil ujicoba ahli media dengan nilai 3.07, yang berarti memiliki kriteria baik, hasil ujicoba ahli materi dengan nilai 3.40, yang berarti memiliki kriteria baik, hasil ujicoba ahli desain pembelajaran dengan nilai 3.40 yang berarti memiliki kriteria baik. Sedangkan pada ujicoba one to one dengan nilai 3.33, yang berarti memiliki kriteria baik, hasil ujicoba small group dengan nilai 3.31, yang berarti memiliki kriteria baik dan hasil uji coba field test 3.18. sehingga rata-rata keseluruhan dari evalusi para ahli dan ujicoba peserta didik memiliki persentase 82.04 %, yang berarti software berhitung dalam pembelajaran matematika yang diberi nama kalkulator bangun datar dan bangun ruang dapat dikategorikan baik.